A facile preparation of submicro-sized Ti2AlC precursor toward Ti2CTx MXene for lithium storage. (10th November 2022) - Yang, Ling Xu; Mu, Yong Biao; Liu, Rui Jia; Liu, Hui Jun; Zeng, Lin; Li, Hong Yi; Lin, Guang Qiang; Zeng, Chao Liu; Fu, Chao
Highlights: Submicron-sized Ti2 AlC powder was firstly synthesized in large quantities by a modified molten salt method. Ti2 CTx MXene is obtained by etching Al from the Ti2 AlC in 8% HF solution for 2 h. The as-synthesized Ti2 CTx MXene exhibited superior electrochemical performances as an anode in LIBs. It is a new insight into the preparation of Ti2 AlC precursor toward Ti2 CTx MXene for lithium storage. Abstract: MXenes, a new class of two-dimensional (2D) materials, have drawn special attention as potential anode materials for lithium-ion batteries (LIBs) in the last decade. However, the productization is primarily restricted by the scalable preparation of their parent MAX phases. Moreover, decreasing the particle size of the precursor powder could dramatically enhance the etching efficience. Furthermore, the fine-grained MAX phases are beneficial for improving the electrochemical performance of MXenes. Therefore, herein we report a facile and high-efficiency method to synthesize submicron-sized Ti2 AlC powder in molten (Na, K)Cl in large quantities. As a result, Ti2 CT x MXene powder was attained by almost complete removal of Al layer from the above precursor in 8% HF solution for 2 h at room temperature. The as-prepared Ti2 CT x MXene exhibited superior performance as an anode material for LIBs with a sustainable discharge capacity of ∼260 mAh‧ g   −   1 at 100 mA‧ g   −   1 in 120 cycles and a discharge capacity of 216 mAh‧ g   −   1 at 500 mA‧ g   −   1 with an excellent capacity retention of 96.13% after 540 cycles. The prominent performance of Ti2 CT x as an anode material for LIBs is due to the introduction of high-density surface functional groups during etching of the submicron-sized Ti2 AlC and enhanced density of edges, which provide more effective adsorption sites for Li ions.